Water Crisis in Spain: Drought, Decreasing Water Reserves, and Its Impact on Society and the Economy - Akbar, Amru; Siahaan, Hana Margaretha; Aulia, Nurul Rahma (EL-JUGHRAFIYAH, 2024)
This research aims to identify the factors causing the water crisis in Spain, analyze its impact on society and the economy, and evaluate solutions that can be implemented. The research methodology uses library or literature studies and involves secondary data analysis. Key findings show that drought, declining water reserves and climate change are the main factors in Spain's water crisis, which impacts public health, the agricultural sector and social stability. Based on these findings, it is concluded that collaborative measures between government, society and relevant sectors are needed to address this water crisis effectively and sustainably to ensure adequate water availability for Spain in the future.